Reducing the morbidity of parotidectomy for benign pathology. Issue 11 (2nd June 2020) - Petrides, George A.; Subramaniam, Narayana; Pham, My; Clark, Jonathan R.
Abstract: Background: Conservative surgical approaches, reconstructive techniques and technology are increasingly used in parotid surgery. The aim of this study was to determine the surgeon‐modifiable factors which impact the rates of post‐operative complications following parotidectomy for benign pathology. Methods: A retrospective cohort study of patients undergoing parotidectomy for benign pathology by or under the supervision of the senior author between 2006 and 2019 was performed. Clinicopathological variables, operative techniques and post‐operative complications were recorded using standardized templates. Multivariable logistic regression models were used to obtain odds ratios (ORs) whilst adjusting for the effect of other clinically relevant covariates. Results: In total, 357 parotidectomies were performed. Independent factors associated with post‐operative facial paresis were re‐operative surgery (OR 3.51, 95% CI 1.19–10.33, P = 0.023), nerve integrity monitoring (OR 0.50, 95% CI 0.26–0.99, P = 0.046) and operation type, with focused tumour dissection (FTD) having the lowest rate of paresis (OR 0.19, 95% CI 0.040–0.92, P = 0.038) compared to limited parotidectomy. Factors associated with reduced wound complications on adjusted analysis were dermofat grafting (OR 0.10, 95% CI 0.01–0.72, P = 0.023), lesion size (OR 0.68, 95% CI 0.50–0.92, P = 0.01) and FTD (OR 0.16, 95% CI 0.05–0.59, P = 0.005) compared to limited parotidectomy. Conclusion: FTD, nerve integrity monitoring and dermofat grafting are surgeon‐modifiable variables associated with lower rates of post‐operative complications following parotidectomy for benign pathology. However, the benefit of these operative techniques relies on their appropriate utilization by performing surgeons. Abstract : The aim of this study was to determine the surgeon‐modifiable factors which impact the rates of post‐operative complications following parotidectomy for benign pathology. Focused tumour dissection, nerve integrity monitoring and dermofat grafting are surgeon‐modifiable variables associated with lower rates of post‐operative complications following parotidectomy for benign pathology. However, the benefit of these operative techniques relies on their appropriate utilization by performing surgeons.